13x + 15 = 11x - 5
2x = -20
x = -10
Chat with our AI personalities
2x2+13x+15 = (2x+3)(x+5)
7x-5+2x=3-4x+12 7x+2x-5=3+12-4x 9x-5=15-4x 9x+4x-5=15-4x+4x 13x-5=15 13x-5+5=15+5 13x=20 13x/13=20/13 x=20/13
2x^2 + 13x + 15 factored means that the two numbers must multiply to the constant (15) and add to equal the coefficient on the X (13). So it becomes: (2x + 3) (x + 5). If expanded, 2x*5 = 10x and 3 * x = 3x which add to 13x. And 5 * 3 = 15
It equals 285
2x + 5y = 2 ..... Eq.1-3x - y = -3 ..... Eq.2 .... we can write it in another form y = 3 - 3xPut the value of y in Eq.1 the result will be :2x + 5(3 - 3x) = 22x + 15 - 15x = 22x - 15x + 15 = 2-13x + 15 = 2-13x = 2 - 15-13x = -13x = -13/-13 ......... X = 1to find Y, put the value of X in Eq.2y = 3 - 3xy = 3 - 3(1)y = 3 - 3 .......... Y = Zero